Explosions of blue supergiants from binary mergers for SN 1987A. Issue 1 (3rd October 2018) - Menon, Athira; Utrobin, Victor; Heger, Alexander
Abstract: Based on the work of Menon & Heger, we present the bolometric light curves and spectra of the explosions of blue supergiant progenitors from binary mergers. We study SN 1987A and two other peculiar Type IIP supernovae: SN 1998A and SN 2006V. The progenitor models were produced using the stellar evolution code kepler and then exploded using the 1D radiation hydrodynamic code crab . The explosions of binary merger models exhibit an overall better fit to the light curve of SN 1987A than previous single star models because of their lower helium-core masses, larger envelope masses, and smaller radii. The merger model that best matches the observational constraints of the progenitor of SN 1987A and the light curve is a model with a radius of 37 R_ , an ejecta mass of 20.6 M_ , an explosion energy of 1.7× 10^51 erg, a nickel mass of 0.073 M_ , and a nickel mixing velocity of 3\!000 km s^-1 . This model also works for SN 1998A and is comparable with earlier estimates from semi-analytic models. In the case of SN 2006V, however, a model with a radius of 150 R_ and ejecta mass of 19.1 M_ matches the light curve. These parameters are significantly higher than predictions from semi-analytic models for the progenitor of this supernova.